Alternative Mechanism to Deal with Stressful Condition: Do We Really have a Social Support? - Sugiarti Agus Musabiq; Siska Aris Nur Fitri (Journal of Educational, Health and Community Psychology, 2021)
This study aims to determine the role of health promoting behavior as a mediator of the relationship between perceived social support and psychological distress in poor young adults in DKI Jakarta. The research data collection was directly conducted by visiting the participants, young adults with age 8-29 years old (N = 314). The research instruments used were HPLP II, Social Provision Scale (SPS), Symptom-25 Checklist (HSCL-25). The results of the mediation analysis showed the significancy that health promotion behavior partially mediated the relationship between perceived social support and psychological distress, with indirect effects (Î² = .003, p = <.01) and direct effects (Î² = -.022, p = <. 01 ). Thus, perceived social support can directly increase psychological distress or through health promotion behavior first. People who perceive themselves get social support will have feeling that are cared for and loved, so that they will motivate themselves to be involved in healthy behavior and reduce psychological distress.Â Â